Implementing Intergenerational Youth Ministry within Existing Evangelical Church Congregations: What have we Learned? - Snailum, Brenda (Christian education journal, 2012)
In this modified Delphi study, a panel of four intergenerational ministry experts was interviewed to determine specific factors critical to consider when establishing intergenerational youth ministry within an existing congregation. Their recommendations included (a) make intergenerational community a core value, (b) balance intergenerational with age-specific ministry, (c) make sure all leadership is fully vested, (d) educate the congregation, (e) begin where you are, (f) be intentional and strategic, and (g) include all generations and ministry venues. Hindrances included (a) failure to transition to an intergenerational paradigm, (b) lack of understanding the basis/need for intergenerational ministry, and (c) self-centeredness.